Orthorectic behavior among students and motivation for physical activity, dietary habits, and restrictive eating - Rozmiarek, Mateusz; Grajek, Mateusz; Krupa-Kotara, Karolina; Malchrowicz-Mośko, Ewa (Frontiers in Nutrition, 2024)
Orthorexia lacks official recognition as an eating disorder; however, orthorexic behaviors, associated with a stringent selection of food, may serve as a predisposing factor to the development of eating disorders. It is characterized by an obsessive preoccupation with healthy eating and strict dietary standards, often prevalent in high-risk groups such as athletes and individuals concerned with their physical appearance. The objective of this study was to evaluate the incidence of orthorexia among students exhibiting varying lifestyles (including dietary habits and levels of physical activity, along with their respective motivational factors). The research involved 600 participants equally distributed between health-related (HRF) and non-health-related (NRF) academic categories, with the majority of participants in the HRF category being women. Assessments included BMI calculations, dietary evaluation based on Polish standards, categorization of physical activity levels, the EMI-2 questionnaire on motivation to exercise, the DOS test for orthorexia propensity, and the TFEQ-13 questionnaire for eating behavior. Results showed that primary motivators for physical activity included disease prevention, health maintenance, strength/endurance, and physical appearance. Orthorexia tendencies were prevalent, particularly in the HRF group, linked to lower BMI, better diet quality, higher physical activity levels, and a higher prevalence of restrictive eating. In conclusion, students in health-related fields, driven by a strong health consciousness, are at risk of orthorexia. This emphasizes the need for balanced health education and support. Orthorexic tendencies are associated with distorted perceptions of food portions and calories, underscoring the importance of awareness and intervention.